Implicit and explicit changes in body satisfaction evoked by body size illusions: Implications for eating disorder vulnerability in women. - Catherine Preston; H Henrik Ehrsson (PLoS ONE)
Dissatisfaction with one's body is a widespread issue in modern society and has been linked to vulnerability for developing eating disorders. Recent studies have demonstrated a direct relationship between body perception and body satisfaction by manipulating perceived body size using multisensory body illusions. However, how these body size illusions influence implicit affective experience has not previously been examined. The current experiment used an established full-body ownership illusion paradigm to induce feelings of illusory obesity in male and female participants. The effects of illusory obesity on explicit and implicit body satisfaction were measured in naïve participants across two separate experiments. In terms of explicit measures, owning an obese body decreased body satisfaction, and owning a slimmer body increased body satisfaction in females but not in males. However, implicit feelings regarding the body were only influenced by the synchrony of the touch and not the size of the body in the illusion. These results suggest that implicit and explicit affective experiences of the body may be mediated by different factors. In addition, these findings may have clinical implications because both implicit and explicit changes in affective experience of the body were related to behaviours and thoughts associated with disordered eating in a non-clinical sample.